The Role of H5P-Based Interactive Media in The Mathematics Learning Process - Wandra Irvandi; Yudi Darma (Riemann: Research of Mathematics and Mathematics Education, 2025)
Educational transformation in the digital era utilizes various technologies to improve the quality of learning and provide innovative learning experiences. This use of technology not only changes the way we learn and teach but also creates a more adaptive and responsive educational environment in the digital era. This study focuses on the integration of interactive media based on H5P to improve mathematical problem-solving skills. The research method used a literature review to examine the relationship between technology and mathematical problem-solving skills. The results show that interactive media based on H5P can be utilized to make learning more innovative. The media meets the criteria of validity, practicality, and effectiveness, making it suitable for use in the learning process.